RESEPSI MAHASISWA TERHADAP PEMBERITAAN ANIES BASWEDAN SEBAGAI CALON PRESIDEN - Siregar, Ballian; Abdullah, Ahmad Zaki; Solihin, Olih (Jurnal Common, 2022)
The information media influences public attitudes in many aspects of life, including those concerning public political attitudes. Therefore the position of the media is very strategic in mapping public political attitudes. The media carrying the message constructs the message it makes. This study aims to analyze student reviews of the media coverage of Anies Baswedan as a presidential candidate in 2004. This study was designed with a qualitative approach, reception analysis method. Data collection techniques were obtained through surveys, literature review and documentation. The results of the study show that students have various attitudes after they learn about media coverage. Students who have a dominant-hegomonic position have reasons that Anies Baswedan is the best figure currently available; students who are in a negotiated position choose the moderate path to be more careful with the reason that they will first study the political figures that will appear ahead of the upcoming 2024 Indonesian presidential election; students who took an oppositional position without hesitation immediately rejected him on the grounds that Anies Baswedan was not fit to be president of Indonesia. Keywords: Reality construction, social construction, student response, Anies Baswedan